Vine death of Hort 16A in Chile caused by Verticillium alboatrum - Fullerton, R.A.; Auger, J.; Rodriguez, I.; Manning, M.A.; Martin, R.A.; Duboy, F. (New Zealand Plant Protection, 2008)
GOLD kiwifruit Actinidia chinensis Hort 16A is being grown under licence in Chile as part of the ZESPRI global supply strategy for the cultivar The first plantings were made in 2003 Vines started dying within 2 years and by May 2007 up to 50 of vines had died in the older orchards The problem is continuing The disease is caused by Verticillium alboatrum a soilborne pathogen that infects the roots subsequently invading the whole plant Apparently healthy plants suddenly develop necrotic patches on leaves and the whole plant wilts and dies Other symptoms include cracking of the bark brown discoloration of vascular tissues and profuse growth of watershoots from the rootstock and lower scion This is the first record of this fungus causing a serious disease in kiwifruit A number of remedies including soil and trunk injections with fungicide and soil fumigation for replant sites are being evaluated